Pengaruh Kompetensi dan Profesionalisme Terhadap Kinerja Penyuluh Pertanian dengan Kepuasan Kerja Sebagai Variabel Moderasi pada Dinas Pertanian Kota Payakumbuh - Sri Polya Kettipusem; Jerry Heikal (Fakultas Tarbiyah dan Ilmu Keguruan, IAI Sultan Muhammad Syafiuddin, 2024)
The Payakumbuh City Agricultural Service is one of the regional apparatus organizations which plays a role in providing direct services to the farming community, which is responsible for increasing the production of agricultural products which are useful for food supply as well as in terms of improving the welfare of farmers. So, competent, professional and high-performing Agricultural Extension Workers are needed as the front guard in increasing farmer competency. This research aims to predict the influence of Competency and Professionalism of Instructors on the Performance of Agricultural Instructors at the Payakumbuh City Agricultural Service with Job Satisfaction as a moderating variable. The samples used in this research were 43 samples consisting of all agricultural instructors at the Payakumbuh City Agriculture Service. In this research there are 2 (two) independent variables and one Dependent variable (Y) and one Moderation variable (Z). From the processing results there are 2 (two) significant variables, namely professionalism and competence. Meanwhile, job satisfaction did not succeed in moderating the relationship between competency and performance, but job satisfaction had a significant effect on weakening the relationship between professionalism and the performance of agricultural instructors at the Payakumbuh City Agriculture Service